Teachers’ Competence in Teaching Science: A Cornerstone for Professional Development. - Guinid, Jennifer (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the teaching competence of Grade 5 teachers teaching Science in Ambaguio, Nueva Vizcaya, focusing on their knowledge, skills, attitudes, and the factors affecting their competence. Anchored on the Input-Process-Output (IPO) framework, the study employed a descriptive research design using a researcher-made, validated questionnaire administered to purposively selected Science teachers. Data were analyzed using frequency, percentage, and weighted mean to describe the respondents’ profile and evaluate their teaching competence. The findings revealed that the respondents were predominantly experienced, middle-aged, married female teachers who actively pursued professional development and demonstrated strong commitment to the teaching profession. The respondents exhibited a very evident level of competence in terms of knowledge (WM = 4.65), skills (WM = 4.64), and attitudes (WM = 4.40), particularly in lesson planning, content development, instructional delivery, communication, learner engagement, collaboration, fairness, and professionalism. However, the factors affecting teaching competence were perceived as moderately serious (WM = 2.70), with administrative workload, limited instructional resources, insufficient training opportunities, unclear operational procedures, and performance appraisal processes identified as the primary concerns. The study concluded that while Science teachers demonstrate a high level of teaching competence, continuous institutional support and professional development remain necessary to sustain and further enhance instructional effectiveness. Accordingly, the study recommends continuous professional development, strengthened collaboration among teachers, improved administrative support, adequate instructional resources, enhanced parent-school communication, mentoring initiatives, and regular feedback mechanisms to further improve teaching competence. This study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting teacher competence as a key component of quality Science instruction. It also contributes to educational and institutional sustainability by providing evidence that can guide teacher development initiatives, strengthen instructional practices, and promote continuous improvement in educational quality.